THE INFLUENCE OF AGRICULTURAL SECTOR VARIABLES ON THE ECONOMIC GROWTH OF INDONESIA: AN ISLAMIC ECONOMIC PERSPECTIVE - Andri Juansya; Musthofa, M. Wakhid; Desfitranita, Desfitranita (Universitas Muhammadiyah Prof DR HAMKA, 2024)
This research aims to assess the impact of the agricultural sector (plantation crops, livestock, and fisheries) on Indonesia's economic growth using time series data extracted from the reports of the Central Statistics Agency (BPS) from 2011 to 2022. The analytical method employed is a quantitative approach utilizing multiple linear regression models, with classical assumption tests conducted prior to data analysis. Data analysis for this study is conducted using EViews version 10 software. The findings indicate that plantation crops do not have a significant impact, with a probability value of 0.5168 > 0.05. However, livestock and fisheries show significant impacts, with probability values of 0.0222 < 0.05 and 0.003243 < 0.05, respectively. Furthermore, the R-squared test results demonstrate that the independent variables can explain 77.77% of the variance in the dependent variable. Keywords: Agricultural Sector (plantation crops, livestock, fisheries), Indonesian Economic Growth.